2009
DOI: 10.1124/jpet.109.154245
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Selectivity of the Mammalian Bombesin Peptide, Neuromedin B, for Its Receptor

Abstract: The mammalian bombesin (Bn) peptides, neuromedin B (NMB) and gastrin-releasing peptide (GRP), have widespread actions in many tissues, and their effects are mediated by two closely related G-protein-coupled receptors, the NMBR and GRPR. Little is known about the structural determinants of NMBR selectivity for NMB, in contrast to GRP selectivity for the GRPR, which has been extensively studied. To provide insight, chimeric NMBR-GRPR loss-of-affinity and gain-of-affinity mutants were made, as well as NH 2 -termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…This conclusion is shown by the finding that with the cyclopentapeptide antagonist, FC131 for the CXC4 chemokine receptor [57] or with the agouti-related protein antagonist of the melanocortin-4 receptor [57], high receptor affinity/selectivity was due to differences in interaction with the EC2 and EC2/EC3 respectively, and with the VPAC1 peptide receptor antagonist, Ac-His 1 [DPhe 2 ,Lys 15 ,Arg 16 ,Leu 27 ] VIP(3–7)/GRF(8–27) , its selectivity was due to differences in the amino terminal VPAC receptor domain[58]. Our results are generally similar to findings in other studies on BnRs which show differences in both EC regions and in upper TM regions are important for the high affinity/selectivity of various BB 3 receptor selective peptide agonists, as well as GRP and NMB for BB 2 and BB 1 receptors, respectively [41,44,48,56,5961]. Our results with the peptide antagonist, Bantag-1, are also similar to findings with various peptide agonist ligand’s interaction with other gastrointestinal/neurotransmitter GPCRs, such as CCK-8 with CCK-B receptors [62], neuropeptide S for the neuropeptide S receptor [63], substance P for the neurokinin-1 receptor [64], [D-Ala 2 ,MePhe 4 ,Gly 5 -ol]encephalin (DAMGO) for μ opioid receptor [65] or CCK8 for CCKB receptor [62], all of which also require interaction with EC domains and transmembrane regions for selectivity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This conclusion is shown by the finding that with the cyclopentapeptide antagonist, FC131 for the CXC4 chemokine receptor [57] or with the agouti-related protein antagonist of the melanocortin-4 receptor [57], high receptor affinity/selectivity was due to differences in interaction with the EC2 and EC2/EC3 respectively, and with the VPAC1 peptide receptor antagonist, Ac-His 1 [DPhe 2 ,Lys 15 ,Arg 16 ,Leu 27 ] VIP(3–7)/GRF(8–27) , its selectivity was due to differences in the amino terminal VPAC receptor domain[58]. Our results are generally similar to findings in other studies on BnRs which show differences in both EC regions and in upper TM regions are important for the high affinity/selectivity of various BB 3 receptor selective peptide agonists, as well as GRP and NMB for BB 2 and BB 1 receptors, respectively [41,44,48,56,5961]. Our results with the peptide antagonist, Bantag-1, are also similar to findings with various peptide agonist ligand’s interaction with other gastrointestinal/neurotransmitter GPCRs, such as CCK-8 with CCK-B receptors [62], neuropeptide S for the neuropeptide S receptor [63], substance P for the neurokinin-1 receptor [64], [D-Ala 2 ,MePhe 4 ,Gly 5 -ol]encephalin (DAMGO) for μ opioid receptor [65] or CCK8 for CCKB receptor [62], all of which also require interaction with EC domains and transmembrane regions for selectivity.…”
Section: Discussionsupporting
confidence: 90%
“…Our results differ from previous studies of other BnRs (BB 2 and BB 1 receptors) investigating the importance of the different EC domains for ligand selectivity using a similar chimeric receptor approach. In these studies the selectivity of the native agonist ligand GRP for BB 2 receptor and NMB for BB 1 receptor, are primarily affected by differences in EC2 [43,56]; whereas the high BB 2 receptor selectivity of two peptide antagonists (JMV591, JMV641)[42] are primarily to differences in the EC3, with a small contribution from EC1 and for the BB 1 receptor peptoid antagonist, PD168368, no EC domains were involved in determining selectivity, instead it was determined primarily by differences in TM5 [53]. These results also differ from BnR chimeric studies investigating the importance of the EC domains for the selectivity of two peptide agonists for BB 3 receptor over BB 2 receptor /BB 1 receptor, finding primarily differences in EC2 were the most important [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is limited data in the literature on the NMB receptor in other species, our human data are consistent with studies in rat tissues [4,37,46]. NMB is reported also to have a very high affinity (IC 50 -0.4 nM) for the rNMBR in rat esophageal muscle [90] or rNMBR transfected Balb cells [20] and in most, but not all studies to be equipotent to litorin and >50 fold more potent than Bn and >200 times more potent than GRP [4,37,46]. For the 12 synthetic Bn analogues only peptide #10 [Tables 1–3, D-Phe 6 , βAla 11 , Phe 13 , Nle 14 ] Bn(6–14)] and its D-Tyr 6 analogue (peptide #9, Tables 1–3) had very high affinity (<1 nM) for the hNMB receptor which is similar to data reported for the rat NMB receptor [46,55,62].…”
Section: Discussionsupporting
confidence: 87%
“…First, the amino acid was predicted to lie in either the outer one-third of the transmembrane (TM) helix or in the extracellular domain of the receptor, because the initial interaction of peptide ligands generally occurs in these receptor regions. Second, because previous studies showed the N-terminus of the GRP or NMB receptors are not essential for high affinity GRP or NMB binding, respectively [38–40], only the receptor regions corresponding to the receptor region from TM2 to the carboxyl terminus of the Bn receptors were investigated. Third, amino acids, which were in the same position from TM2 to the carboxyl terminus of the aligned receptors, which had high affinity for Univ.Lig.…”
Section: Methodsmentioning
confidence: 99%
“…hGRP receptor point mutants were constructed by using the Quick-Change Site-Directed Mutagenesis Kit, following the manufacturer’s instructions with minor modifications as described previously [26,40]. Each amino acid which was possibly important for Univ.Lig high affinity binding identified as described using the above selection criteria was mutated one at a time to the comparable amino acids in either hCCK A R, alanine or another amino acid depending on the criterion used.…”
Section: Methodsmentioning
confidence: 99%